Evaluasi Penggunaan Alat Pelindung Diri (Apd) Pada Perawat di Unit Gawat Darurat (Ugd) Rumah Sakit Mesra Tahun 2025 - Rizki Samur; Nofiyadi Nofiyadi; Herniwanti Herniwanti (Universitas Pahlawan Tuanku Tambusai, 2026)
The use of Personal Protective Equipment (PPE) is an important component in preventing infection transmission, especially for nurses working in the Emergency Unit (ER) with high risk. Occupational Safety and Health (OSH) is an important aspect in every work environment in the world as an effort to prevent accidents and health problems due to work. This study aims to evaluate the level of compliance and effectiveness of the use of personal protective equipment (PPE) among nurses in the Emergency Unit (ER) of a hospital. The methods used include observation, interviews, and risk analysis using the USG and Fishbone Analysis approaches. The results of the study indicate that there are still shortcomings in aspects of human resources, standard operating procedures (SOP), supervision, facilities, and budget limitations that have the potential to increase the risk of accidents and exposure to occupational hazards. Conclusion: that although some nurses have implemented the use of PPE correctly, there is still a need for continuous education, supervision, and the provision of PPE facilities to improve occupational safety in the ER. It is hoped that the results of this study will be the basis for policy making related to occupational safety and health at Mesra Hospital